Antineoplasic chemotherapy extravasation prevent: an integrative review - Marizete Tavares Ferreira; Paula Elaine Diniz dos Reis; Isabelle Pimentel Gomes (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Skin toxicity resulting from extravasation of chemotherapy is a major adverse effect that demand more rigorous care from oncology nurses. This study aimed to identify evidence in the scientific literature related to the prevention of leakage in patients with peripheral intravenous infusion of vesicant chemotherapy. We performed an integrative review of the literature. The seven eligible studies presented strategies for prevention, consisting in evaluation of the patient, proper training of the nursing team and adequate assessment on existing conditions for the venous access. The authors conclude that studies testing new forms of effective prevention are eagerly expected, in order to provide better evidence for decision-making and clinical support, and to prevent the extravasation of vesicant drugs in patients  experiencing  peripheral intravenous chemotherapy.